Microbiological evaluation of vitamin C rich acerola mediated silver and copperoxide nanogel in treatment of periodontitis with and without diabetes mellitus - C. Burnice Nalina Kumari; N. Ambalavanan; S. Rajesh Kumar; Jaideep Mahendra; Uma Sudhakar (Elsevier, 2024)
Aim: Nanotechnology presents a promising approach for managing chronic periodontitis, a common oral disease characterized by gum inflammation and loss of supporting bone around teeth. This study aimed to evaluate the antimicrobial efficacy of acerola-mediated silver nanoparticles (AgNPs) gel and copper oxide nanoparticles (CuONPs) gel in periodontitis patients with and without diabetes. Materials and methods: The antimicrobial efficacy of acerola-mediated AgNPs gel and CuONPs nanogel was assessed using the agar well diffusion technique, Minimum Inhibitory Concentration (MIC) assay, Minimum Bactericidal Concentration (MBC) analysis, time-kill curve assay, and cytoplasmic and protein leakage analysis from periodontitis patients with and without diabetes. Results: The study found that acerola-mediated AgNPs gel demonstrated more consistent and effective antimicrobial activity against periodontitis, with lower MIC and MBC values compared to the CuONPs gel, across all tested concentrations. These results suggest that acerola-mediated AgNPs gel may be a more effective and targeted therapeutic agent for periodontal disease management. Conclusion: The findings emphasize the importance of nanoparticle gel concentration in optimizing periodontal treatment outcomes. Acerola-mediated AgNPs gel, with its superior efficacy and consistency in bactericidal activity, shows significant potential for periodontal therapy. Clinical significance: Innovative nanoparticles like copper and silver oxides exhibit antibacterial, anti-inflammatory, and antioxidant properties, making them promising agents for targeting periodontal pathogens. Acerola (Malpighia emarginata), with its high vitamin C content and antioxidant properties, is beneficial in mitigating oxidative stress associated with chronic periodontitis.